Targeted UDP-glucose ceramide glucosyltransferase stable overexpression induces a metabolic switch improving cell performance at high cell density - Rahimi, Marzia; Nielsen, Lars K.; Lavado-García, Jesús (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundViral vectors such as adeno-associated viruses (AAVs) and virus-like particles (VLPs) are critical tools in gene therapy, typically produced using transient gene expression (TGE). Intensification of TGE processes to high cell densities is hampered by the cell density effect (CDE), characterized by decreased cell-specific productivity as cell density increases. Physiological changes following transfection, particularly reduced glycosphingolipid biosynthesis, have been identified as factors affecting productivity and viability.MethodsWe used a targeted integration approach to generate HEK293SF-3F6 cell lines constitutively or inducibly overexpressing UDP-glucose ceramide glucosyltransferase (UGCG), the precursor enzyme responsible for glycosphingolipid biosynthesis. We evaluated how varying UGCG expression levels influenced cellular metabolism, transfection efficiency, and HIV-1 Gag VLP production.ResultsConstitutive UGCG overexpression triggered a metabolic shift from glycolysis toward mitochondrial fatty acid oxidation. Moderate UGCG expression improved transfection efficiency and enhanced VLP production at high cell densities, while high UGCG expression negatively impacted cellular performance. Inducible UGCG expression further enhanced productivity under high-density conditions, highlighting the advantages of tightly regulated transgene expression.ConclusionThese findings highlight crucial metabolic adaptations linked to UGCG expression in production cell lines and underscore the value of carefully controlled UGCG expression levels for optimizing viral vector and VLP manufacturing.